Pengembangan Desa Ekowisata Bahoi melalui Atraksi, Amenitas, dan Aksesibilitas Pasca Pandemi COVID-19 - Roosalina Hera Lucia; Steven Yones Kawatak; Fiolentin Shania Putri Pianaung (Jurnal Informatika Ekonomi Bisnis, 2023)
Competition in the tourism sector to fight over tourists is starting to heat up again with the end of the COVID-19 pandemic in Indonesia. This also applies to the Bahoi Ecotourism Village located in Likupang, which is now one of the Special Economic Zones. This research was conducted with the aim of knowing the extent of the readiness of the Bahoi Ecotourism Village in preparing attractions, amenities and accessibility and also to formulate various alternatives that could become development strategies in this tourist destination. Data was collected through interviews with representatives of local residents, local government and business people around the village. The analysis was carried out using the SWOT method to determine internal and external factors and then became the basis for developing a Strategy Matrix. The results of the study show that from internal factors there are various strengths possessed by the Bahoi Ecotourism Village, such as the existence of interesting natural and cultural tourist attractions, but there are also several weaknesses, for example facilities are still limited. While the external factors encountered were the presence of several opportunities, including increased interest in visiting the village and government support, but also the existence of several threats, such as environmental damage and negative social change. Based on these findings, several strategies were formulated that could be developed, for example optimizing existing attractions and improving existing facilities and infrastructure.